Dani Bolognesi Oral History Interview, 2019 - Bolognesi, Dani (2019)
This oral history was conducted with Dr. Dani Bolognesi on May 29, 2019 by Taylor Patterson as part of the Dr. David Sabiston Oral History Project. During the interview, Bolognesi discusses his early life and education; his studies and work at Duke, where he was a student under Dr. Joseph Beard; professional and personal memories of Dr. David Sabiston, including Sabiston's interest in grants; Sabiston's stoke; Sabiston's Christmas parties; translational research; the Department of Surgery; and Bolognesi's HIV research.